2010
DOI: 10.1111/j.1365-2303.2010.00818.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative evaluation of sentinel lymph nodes in breast cancer: comparison of frozen sections, imprint cytology and immunocytochemistry

Abstract: In our study the combined accuracy of the three methods was the same as combining touch imprint cytology and frozen sections or touch imprint cytology plus rapid immunocytochemistry. Rapid immunocytochemistry provides an additional parameter and preserves tissue for permanent sections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 39 publications
2
17
0
5
Order By: Relevance
“…False-positive results that could lead to unnecessary ALND are very rare. The sensitivity of 90% of our research compares favorably with other reported studies of IC and FS 12,22,23. Therefore, IC is definitely an easy, quick, sensitive, and accurate method for the intraoperative assessment of SLN in BC patients.…”
Section: Discussionsupporting
confidence: 77%
“…False-positive results that could lead to unnecessary ALND are very rare. The sensitivity of 90% of our research compares favorably with other reported studies of IC and FS 12,22,23. Therefore, IC is definitely an easy, quick, sensitive, and accurate method for the intraoperative assessment of SLN in BC patients.…”
Section: Discussionsupporting
confidence: 77%
“…[8][9][10][11][12][13][14][15] To improve the intraoperative detection of metastatic carcinoma in SLNs, several investigations have shown the efficacy of immunohistochemical evaluation with anti-CK antibodies. Generally, the sensitivity of frozen sections with immunohistochemistry 14,[27][28][29] is better than that of TIC with immunohistochemistry [20][21][22][23][24][25][26] as well as nonimmunohistochemical examinations. Because the SDB method does not depend on the skill of pathologists in detecting metastasis by cytological and pathological examinations, it may standardize the diagnostic procedure of metastasis to the SLN in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, intraoperative touch imprint cytology (TIC) has lower sensitivity in detecting metastasis of SLNs compared with pathological examinations . Therefore, to improve the sensitivity of intraoperative evaluation of SLNs in breast cancer, intraoperative rapid cytokeratin (CK) immunostaining is used with frozen sections or TIC …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, formalin induces significant chemical alterations that lead to loss of integrity of the biomolecules in the specimens and compromises many downstream molecular tests [36,37]. Alternatively, snap-freezing tissue samples better preserves the integrity of tissue biomolecules; however, frozen tissues require special conditions for storage and handling, and also result in lower histological quality, thus the pathological evaluation of frozen sections can be difficult for many diseases [38].…”
Section: Box 1 Pathology Surgical Pathologists and Cytogeneticistsmentioning
confidence: 99%